Photochemistry of aryl halides: Photodissociation dynamics - Han, Ke-Li; He, Guo-Zhong (Journal of photochemistry and photobiology. C, Photochemistry reviews, 2007)
In recent years, the photodissociation dynamics of aryl halides has been a subject of intensive studies, which is closely related to the atmospheric chemistry. Here we present a review on the photochemistry of aryl halides, with emphasis on the recent progress in photodissociation dynamics at 266 nm by using photofragment translational spectroscopy. The ab initio calculations have also been employed to investigate those photodissociation processes. It has been found that the photodissociation of aryl halides at 266 nm is attributed to the nonadiabatic process via intersystem crossings from bound singlet excited state to triplet excited state and/or via internal conversion from bound singlet excited state to ground state. Also, the substitution effects in the photodissociation dynamics of aryl halides are discussed.